The possibility of rural tourism in Latakia Governorate (Tariqia Village - Wadi Al-Qal’a) - مخلوف هنادي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Rural tourism is one of the directions that is no less important than other types of tourism, as it includes components and attractions within the framework of tourism investment. Especially since the two areas identified in the study (Tariqia Village and Wadi Al-Qal’a) have distinct natural characteristics that qualify them to be classified as rural tourism with all its characteristics through their nature, availability of water resources, unique climate, and service sectors. If attention is directed towards them, there will be a great opportunity for their development both as rural and tourist destinations, reaching the stage of rural tourism attraction and in turn supporting rural development in Latakia Governorate.